Main Hakim Sendiri atas Nama Kesusilaan: Tinjauan Hukum Pidana dan Hak Asasi Manusia terhadap Praktik Penggerebekan Warga di Rumah Sewa - Andi Aswar; Asia Andi Pananrangi; Reza Alief Andi; Ahmad Nugraha Abrar (Institut Agama Islam Negeri (IAIN) Bone, 2026)
This study examines the practice of community raids against unmarried couples residing in boarding houses and rented housing, which are often justified in the name of enforcing moral norms. Although such practices are framed as efforts to maintain social order, they raise serious legal concerns when conducted without lawful authority and due process. This study aims to analyze the practice of community raids from the perspectives of criminal law and human rights and to assess whether such actions constitute taking or enforcing the law into one’s own hands, which in modern terms is commonly referred to as vigilantism. This study employs normative legal research using statutory and conceptual approaches through the examination of relevant legislation, legal doctrines, and scholarly opinions related to criminal law and human rights. The findings indicate that community raids lack legal authority, may give rise to criminal liability, and violate fundamental human rights, particularly the right to privacy and protection from arbitrary actions. The study emphasizes the necessity of clear normative boundaries on community participation in enforcing morality to ensure consistency with the rule of law and human rights protection. Fenomena penggerebekan oleh warga terhadap pasangan bukan suami istri di kost dan kontrakan kerap dibenarkan atas dasar penegakan norma kesusilaan. Praktik tersebut, meskipun berangkat dari nilai moral dan ketertiban sosial, menimbulkan persoalan hukum serius ketika dilakukan tanpa kewenangan dan prosedur hukum yang sah. Penelitian ini bertujuan menganalisis praktik penggerebekan warga dari perspektif hukum pidana dan hak asasi manusia serta menilai apakah tindakan tersebut dapat dikualifikasikan sebagai bentuk main hakim sendiri (eigenrichting). Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual. Hasil penelitian menunjukkan bahwa penggerebekan warga tidak memiliki dasar kewenangan hukum, berpotensi menimbulkan pertanggungjawaban pidana, serta melanggar hak asasi manusia, khususnya hak atas privasi dan perlindungan dari tindakan sewenang-wenang. Penelitian ini menegaskan perlunya pembatasan normatif terhadap peran warga dalam menjaga ketertiban dan norma kesusilaan agar tetap selaras dengan prinsip negara hukum dan perlindungan hak asasi manusia.